Fraud and fraud detection : a data analytics approach - Gee, Sunder (John Wiley & Sons, Inc., 2015)
This book takes an advanced approach to fraud management, providing step-by-step guidance on automating detection and forensics using CaseWare's IDEA software. Readers will learn to use complex data analysis techniques, including automation scripts, allowing easier and more sensitive detection of anomalies that require further review. You will learn to: understand the different areas of fraud and their specific detection methods; identify anomalies and risk areas using computerized techniques; develop a step-by-step plan for detecting fraud through data analytics; utilize IDEA software to automate detection and identification procedures. The delineation of detection techniques for each type of fraud makes this book a must-have for students and new fraud prevention professionals, and the step-by-step guidance to automation and complex analytics will prove useful for even experienced examiners. --